Unique microRNAs appear at different times during the course of a delayed‐type hypersensitivity reaction in human skin. Issue 12 (27th August 2015) - Gulati, Nicholas; Løvendorf, Marianne B.; Zibert, John R.; Akat, Kemal M.; Renwick, Neil; Tuschl, Thomas; Krueger, James G.
Abstract: Diphencyprone (DPCP) is a hapten that induces delayed‐type hypersensitivity (DTH) reactions. MicroRNAs (miRNAs) are short non‐coding RNAs that negatively regulate gene expression and have been implicated in various inflammatory skin diseases, but their role in DTH reactions is not well understood. We generated global miRNA expression profiles (using next‐generation sequencing) of DPCP reactions in skin of seven healthy volunteers at 3, 14 and 120 days after challenge. Compared to placebo‐treated sites, DPCP‐challenged skin at 3 days (peak inflammation) had 127 miRNAs significantly deregulated. At 14 days (during resolution of inflammation), 43 miRNAs were deregulated and, at 120 days (when inflammation had completely resolved), six miRNAs were upregulated. While some miRNAs have been observed in psoriasis or atopic dermatitis, most of the deregulated miRNAs have not yet been studied in the context of skin biology or immunology. Across the three time points studied, many but not all miRNAs were uniquely expressed. As various miRNAs may influence T cell activation, this may indicate that the miRNAs exclusively expressed at different time points function to promote or resolve skin inflammation, and therefore, may inform on the paradoxical ability of DPCP to treat both autoimmune conditions (alopecia areata) and conditions of ineffective immunity (melanoma).